Rancangan Sistem Informasi Pada Kasir Berbasis Web - Zahra Rashifah; Eko Setia Budi (STMIK Budi Darma, 2022)
11eleven is a business engaged in the culinary field of beverages that offer products made from Matcha and Milk Tea, which is located in Ciputat, South Tangerang City. The operational activities of cashier transactions carried out at this store are still carried out in a long time or conventional way. In the transaction process it is written on a piece of note paper, so that for making a transaction paper paper report is collected then the writing of the report is recorded one by one. The use of this manual system can certainly conclude a lot of problems, such as wrong in providing prices, wrong in the calculation of payments, writing on unclear orders, causing services to buyers to be ineffective and efficient, then loss of sales transactions, damage in the memorandum sales, errors in inputting sales reports, so that reporting is inefficient and effective. From these problems, a computerized information system is needed to solve the problem, namely by implementing a web -based cashier information system. The purpose of making this web -based cashier information system is to facilitate the sales activities as well as operational activities at the 11eleven store. The prototype method is the method used in the creation of this web -based cashier information system. Making this website the author also uses Codeigniter framework and boostrap. With the results of the web -based cashier information system, it is expected to provide convenience in carrying out the assistance activities at the 11eleven store.